Inside art direction interviews and case studies - Brower, Steven (Fairchild Books, an imprint of Bloomsbury Publishing Plc, 2015)
"For many design students, the expectation is that they will one day reach the top of the ladder within a design studio or corporation and become an art director. But what does this mean and how does a design student get there? What does an art director do? How is it different from being a designer? How does one lead and inspire a team, work with freelance designers, illustrators and photographers? How do they sell this work to editors, department heads and clients? Becoming a Successful Art Director answers all these questions for design students and professionals alike. It is at once an illustrated art book, a handbook on how to be creative in this exciting work environment, and a guide to what to expect on entering the workplace. Giving practical, hands-on advice for both beginning and advanced students, It will provide a clear picture for graphic design and illustration students of how to work with art directors and the range of industries where an art director might be employed." -- Provided by publisher.